SİYASETNÂMES AND A SAMPLE OF SİYASETNÂME: ÂDÂB-I SALTANAT - Maksut BELEN (Fırat University, 2019)
“Siyasetnâme”s are works which give information about government administration to rulers. They teach to rulers which has to have, moral and religious principles and methods. There are various means of political words, summarize these meanings: government jobs and land management, programs on making the punishment of those who deserve punishment, regulating public affairs government actions, the inter-state economic and regulation of relations in the cultural field and is carried out. Politics and science professions within the meaning of the word also, be tolerant, express the sense of the people and managed to get along well. To present all the party members and administrators with the traditional sense, a political newspaper executives, even the party that followed with curiosity and found a close correlation between daily political newspaper called the politician. “Âdâb-ı Saltanat” contains full informations concerning administration and moral principles and it shows a characteristic of book of government. In this article from Âdâb-ı Saltanat subjects such as characters of rulers, basics of govermental administration, moral and religious principles.